Zwitterionic liquid (ZIL) coated CuO as an efficient catalyst for the green synthesis of bis-coumarin derivatives via one-pot multi-component reactions using mechanochemistry. (25th April 2017) - Mayank,; Singh, Amanpreet; Raj, Pushap; Kaur, Randeep; Singh, Ajnesh; Kaur, Navneet; Singh, Narinder
Abstract : ZIL@CuO1–3 were developed as a catalyst for the synthesis of bis-coumarins under environmentally benign conditions. Mechanochemistry induced synthesis of bis-coumarin derivatives with more than 90% yield was accomplished. Abstract : A convenient, solvent free strategy for the synthesis of bis-coumarins has been developed using zwitterionic liquid (ZIL ) coated copper oxide (CuO) and mechanical ball milling. TheZIL were fabricated from imidazolium/benzimidazolium and sulfonate/carboxylate based moieties. Use of theZIL offers an interesting multifunctional opportunity to immobilize them over CuO using the anionic part and the cationic part is left freely available for use in catalytic applications. The hybrid catalysts were fully characterized using scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, powder X-ray diffraction, cyclic voltammetry, solid state ultraviolet-visible absorption and spectroscopic emission methods. The threeZIL -based and CuO coupled hybrid catalysts (ZIL@CuO1–3 ) generated were found to have diverse sizes, shapes, photophysical signatures and electrochemical properties. The supramolecular assembly ofZIL and CuO inZIL@CuO1 has extensively enhanced catalytic activity compared to their individual parent components as well as to the two other hybrid materials, ZIL@CuO2–3 . The reaction conditions were optimized by varying the number of balls used, the milling time and the milling speed. The reaction mechanism was elucidated using proton–nuclear magnetic spectroscopy and all the final products were fully characterized using spectroscopic methods. Finally, the performance of the reaction at the multigram scale is also detailed and a high EcoScale score and a low E -factor are the most pleasing features of this methodology, and thus, authenticate its use for eco-friendly synthesis of bis-coumarins and offer advancements over other catalysts described in the literature.